Numerical Investigation of Heat Transfer and Flow Dynamics in Tubes with DNA-Inspired Slotted Inserts - Zhu, Penglong; Sun, Guoxiu; Liu, Ruimeng; Zhou, Sicong; Hu, Baisong; Zhang, Shaofeng (Energies (Basel), 2025)
Within the realm of industrial energy conservation, the optimization of heat exchanger performance is paramount for the augmentation of energy utilization efficiency. This investigation employs computational fluid dynamics (CFD) simulations to elucidate the effects of an innovative DNA-Inspired Slotted Insert (DSI) on the convective heat transfer and pressure drop characteristics within heat exchange tubes. The study provides a thorough analysis of fully turbulent flow (Re = 6600–17,200), examining the effects of various DSI pitches, key lengths, and geometries. The findings reveal that the DSI instigates a three-dimensional spiral flow pattern, which is accompanied by an escalation in the Nusselt number (Nu) and friction factor (f) with increasing Reynolds numbers. An inverse relationship between Nu and both pitch and key length is observed; conversely, f exhibits a direct correlation with these parameters. The study identifies an optimal configuration characterized by a pitch of 10 mm and a key length of 1.5 mm, with square keys demonstrating superior heat transfer performance relative to other geometrical configurations. This research contributes significant design and application insights for double-helical inserts, which are pivotal for the enhancement of heat exchanger efficiency.